2008
DOI: 10.1086/591664
|View full text |Cite
|
Sign up to set email alerts
|

Protostar Mass due to Infall and Dispersal

Abstract: The mass of a protostar is calculated from the infall and dispersal of an isothermal sphere in a uniform background. For high contrast between peak and background densities and for short dispersal time t d , the accretion is ''self-limiting''; gas beyond the core is dispersed before it accretes, and the protostar mass approaches a time-independent value of low mass. For lower density contrast and longer dispersal time, the accretion ''runs away''; gas accretes from beyond the core, and the protostar mass appro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 83 publications
(144 reference statements)
3
37
0
Order By: Relevance
“…For our simulations, it appears that unless cores are formed with very large density contrasts relative to their surroundings, ambient gas will play an important and ongoing role in the core's dynamics. This is in line with models that attempt to consider more continuous distributions of variables between core and environment (Myers 2008 …”
Section: Discussionsupporting
confidence: 81%
“…For our simulations, it appears that unless cores are formed with very large density contrasts relative to their surroundings, ambient gas will play an important and ongoing role in the core's dynamics. This is in line with models that attempt to consider more continuous distributions of variables between core and environment (Myers 2008 …”
Section: Discussionsupporting
confidence: 81%
“…The observed increasing opening angles of outflows with increasing age of the protostar has been interpreted as evidence for the erosion of the protostellar envelope by the outflow (Velusamy & Langer 1998;Arce & Sargent 2006) in part explaining the observed shift in the peak between the core and initial mass function (e.g., Myers 2008). In the models of Visser et al (2009) and shown in Fig.…”
Section: Constraints On Evolutionary Modelsmentioning
confidence: 89%
“…A difficulty with this model is that the accretion continues indefinitely. More recently, Myers (2008) has included a model for a time-dependent dispersal of the protostellar core by protostellar outflows. If the dispersal time is sufficiently short, the protostellar mass converges to a well-defined value.…”
Section: Tapered Accretionmentioning
confidence: 99%